Determining Sexual Dimorphism of Living Aquatic Beetles, Stygoparnus comalensis (Coleoptera: Dryopidae) and Heterelmis comalensis (Coleoptera: Elmidae), Using Internal Abdominal Structures. Issue 4 (24th July 2019) - Kosnicki, Ely
Abstract: The Comal Springs dryopid beetle, Stygoparnus comalensis Barr and Spangler, and the Comal Springs riffle beetle, Heterelmis comalensis Bosse, Tuff, and Brown, are protected by the United States Fish and Wildlife Service (USFWS), and the development of a captive self-propagating refuge is of importance to stakeholders within the Edwards Aquifer. Being able to reliably distinguish the sex of living subjects is desirable for establishing a successful refuge program. Ventrite, elytron, and pronotum measurements of S. comalensis were taken to determine if there were sexually dimorphic allometries. Various lighting techniques were also implemented to see if there were other characters that could potentially be used to distinguish females and males. Measurements were not found to satisfactorily separate sexes; however, lateral lighting was found to consistently illuminate internal abdominal structures of S. comalensis where sternite 8 was viewable in males and the fused gonocoxites were viewable in females. Lateral lighting was used to examine living specimens of H. comalensis, and it was found that sternite 8 could be viewed in both sexes where the anterior strut of females was much longer and discernible from the anterior strut of males. Commentary regarding the use of cameras and photography for observing living subjects is given.